COMMUNICATION STRATEGY OF AL-GEE RENTAL TO ATTRACT CUSTOMER INTEREST - Pradika, Nazha Arga Jaya; kartikasari, Dewi; Krisnawati, Ester (Jurnal Visi Komunikasi, 2025)
This study analyzes Al-Gee Rental’s social media communication strategy in fostering customer engagement and loyalty within the context of Society 5.0. The central issue is how the company integrates digital communication with personal interaction to attract and retain customers. The study aims to assess the effectiveness of digital-based Integrated Marketing Communication (IMC). A qualitative method was employed through in-depth interviews with customers and observation of digital interactions. Findings reveal customer engagement across cognitive (attention and feedback), affective (emotional closeness), and behavioral (retention and active participation) dimensions. The study concludes that Al-Gee’s success lies not only in strategic digital integration but also in sustaining human interaction that strengthens long-term loyalty.